Analysis of the Effect of Transformer Load Balancing on the Reduction Technical Shrinkages in Distribution Substations aAt Feeders JN 05 At PT PLN (PERSERO) ULP JANARATA - Ivan Kristiawan Zega; Dino Erivianto; Muhammad Erpandi Dalimunthe (INFOKUM, 2026)
Electricity is a vital component in supporting activities across various sectors, particularly in industry. The reliability of the power distribution system is crucial to maintaining the continuity of energy supply. However, during the distribution process, power losses (technical losses) frequently occur, primarily due to load imbalance in distribution transformers. This study aims to analyze transformer loading on the JN 05 feeder at ULP Janarata by calculating the load percentage, phase current imbalance, and power losses caused by neutral current. A quantitative approach was used, based on field measurements of 16 transformers under Peak Load Conditions (WBP) and Off-Peak Load Conditions (LWBP). Prior to load balancing, total power losses due to neutral current reached 10,190.37 kWh during LWBP and 3,733.41 kWh during WBP each month. After load balancing was performed between phases, technical losses were reduced by 13,923.77 kWh per month. These results indicate that load balancing is an effective method to reduce power losses and improve the efficiency of the distribution system.